2020
DOI: 10.1101/2020.02.02.929091
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Direct reprogramming of astrocytes to neurons leads to functional recovery after stroke

Abstract: Stroke is the leading cause of adult disability with few treatment options for stroke survivors. Astrocyte reprogramming to neurons enables the targeted in vivo generation of new cells at the site of injury and represents a novel approach for brain repair. A number of studies have demonstrated successful conversion of astrocytes to neurons in various models of brain injury and disease; however, the impact of this strategy on tissue and functional outcome following stroke is not well established. Using AAV deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 49 publications
(73 reference statements)
0
10
0
Order By: Relevance
“…While precise mechanisms behind such high barrier in lineage-traced astrocytes warrant further study, one possibility is that lineage-traced astrocytes require Cre-LoxP-mediated DNA recombination, which involves DNA cutting and annealing. For any healthy cell, DNA cutting and annealing is a kind of DNA damage which may trigger massive cellular responses including DNA methylation and other epigenetic modifications (Karakaidos et al, 2020; Livingston et al, 2020; Loonstra et al, 2001). Given the fact that the lineage-traced astrocytes behave very differently from WT astrocytes in terms of conversion, we strongly advise the entire AtN conversion field to be extra cautious when using lineage-traced astrocytes for reprogramming purpose.…”
Section: Discussionmentioning
confidence: 99%
“…While precise mechanisms behind such high barrier in lineage-traced astrocytes warrant further study, one possibility is that lineage-traced astrocytes require Cre-LoxP-mediated DNA recombination, which involves DNA cutting and annealing. For any healthy cell, DNA cutting and annealing is a kind of DNA damage which may trigger massive cellular responses including DNA methylation and other epigenetic modifications (Karakaidos et al, 2020; Livingston et al, 2020; Loonstra et al, 2001). Given the fact that the lineage-traced astrocytes behave very differently from WT astrocytes in terms of conversion, we strongly advise the entire AtN conversion field to be extra cautious when using lineage-traced astrocytes for reprogramming purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies revealed considerable structural [ 32 ] and functional repair [ 29 , 46 ] in mice after transplanting newborn neurons into the cranium of an ischemia mouse model. NeuroD1-induced astrocyte introduction into the mouse cranium resulted in a 35% lesser reduction in motor cortex volume over 2 months compared to the control group [ 29 ].…”
Section: Transdifferentiation As a Therapy For Ischemic Strokementioning
confidence: 99%
“…NeuroD1-induced astrocyte introduction into the mouse cranium resulted in a 35% lesser reduction in motor cortex volume over 2 months compared to the control group [ 29 ]. By analyzing the forelimb fine movements in mice, NeuroD1 treatment was found to be beneficial in the recovery of motor deficits after ischemic stroke [ 46 ]. NeuroD1 was introduced into the rat amygdala, and auditory fear regulation showed that NeuroD1 was able to rescue the defect of fear memory [ 29 ].…”
Section: Transdifferentiation As a Therapy For Ischemic Strokementioning
confidence: 99%
“…Neurod1 -induced lineage conversion of reactive astrocytes has also been applied to the treatment of a focal stroke model in mice induced using endothelin-1, a vasoconstrictor ( Chen et al, 2020 ; Livingston et al, 2020 ). In both of these studies, Neurod1 -induced the effective transdifferentiation of astrocytes to functional iNs in vivo , and provided a significant enhancement of motor behavior ( Chen et al, 2020 ; Livingston et al, 2020 ). These studies provide important proof-of-concept evidence that a neuronal reprogramming strategy could be applied to the treatment of brain injury.…”
Section: In Vivo Neuronal Reprogramming Of Endogenous Glial Cellsmentioning
confidence: 99%